The Activation of Plasminogen Activator Inhibitor-1 Expression by IL-1β Is Attenuated by Estrogen in Hepatoblastoma HepG2 Cells Expressing Estrogen Receptor α - Kilbourne, Edward J.; Scicchitano, Marshall S. (Thrombosis and Haemostasis, 1999)
A low estrogen status in postmenopausal women is associated with elevated plasma levels of plasminogen activator inhibitor-1 (PAI-1). In this study, the ability of estrogen compounds to regulate PAI-1 expression was determined in a hepatocyte HepG2 cell line made to stably express estrogen receptor α (ERα). In both the wild type and ER expressing HepG2 cells, estrogen had no effect on basal PAI-1 expression. However, in the ER expressing cells the ability of IL-1β to increase PAI-1 mRNA and protein levels was attenuated by 17β-estradiol, tamoxifen and twelve estrogen components of Premarin. In contrast, the mixed agonist/antagonist raloxifene had weak agonist activity and like the pure antagonist ICI 182780, it dose dependently blocked the effect of 17β-estradiol on IL-1β stimulated PAI-1 levels. These results suggest that estrogen agonists may lower PAI-1 levels in vivo by inhibiting cytokine activated PAI-1 expression by an ER dependent mechanism.